A Conserved Phenylalanine Residue of Autographa Californica Multiple Nucleopolyhedrovirus AC75 Protein Is Required for Occlusion Body Formation - Chen, Xingang; Yang, Jian; Yang, Xiaoqin; Lei, Chengfeng; Sun, Xiulian; Hu, Jia (Frontiers in Microbiology, 2021)
Autographa californica multiple nucleopolyhedrovirus (AcMNPV) orf75 (ac75) is a highly conserved gene that is essential for AcMNPV propagation. However, the key domains or residues of the AC75 protein that play a role in viral propagation have not been identified. In this study, sequence alignment revealed that residues Phe-54 and Gln-81 of AC75 were highly conserved among alphabaculoviruses and betabaculoviurses. Thus, Phe-54 and Gln-81 AC75 mutation bacmids were constructed. We found that Gln-81 was not required for viral propagation, whereas mutating Phe-54 reduced budded virus production by 10-fold and impaired occlusion body formation when compared with that of the wild-type AcMNPV. Electron microscopy observations showed that the Phe-54 mutation affected polyhedrin assembly and also occlusion-derived virus embedding, whereas western blot analysis revealed that mutating Phe-54 reduced the amount of AC75 but did not affect the localization of AC75 in infected cells. A protein stability assay showed that the Phe-54 mutation affected AC75 stability. Taken together, Phe-54 was identified as an important residue of AC75, and ac75 is a pivotal gene in budding virus production and occlusion body formation.